MHD flow of a micropolar fluid over a stretchable disk in a porous medium with heat and mass transfer - A. Rauf; M. Ashraf; K. Batool; M. Hussain; M. A. Meraj (AIP Advances, 2015)
This article studies the simultaneous impacts of heat and mass transfer of an incompressible electrically conducting micropolar fluid generated by the stretchable disk in presence of porous medium. The thermal radiation effect is accounted via Rosseland’s approximation. The governing boundary layer equations are reduced into dimensionless form by employing the suitable similarity transformations. A finite difference base algorithm is utilized to obtain the solution expressions. The impacts of physical parameters on dimensionless axial velocity, radial velocity, micro-rotation, temperature and concentrations profiles are presented and examined carefully. Numerical computation is performed to compute shear stress, couple stress, heat and mass rate at the disk.